Participative Design as a Work Methodology in Formal Education and Daily Practices (Revista de Ensino em Artes, Moda e Design, 2020)
In the present work, we present the compilation of an interview conducted by a professorof Higher Education (UFRPE) to another co-worker (Unisinos), the interviewee who reflectsand discusses issues related to Participatory Design (PD). The path of conversation traced bythe professionals covers not only the educational scope but that of everyday life, that is, italso deals with how Participatory Design can be considered pragmatically for the developmentand / or monitoring of practical activities concerning and arising from other dimensionsof everyday life of the social subject. In the course of the construction of thought proposed,terms such as curiosity, proactivity, independence, autonomy, and collectivity were quite recurrentto rethink pedagogical and professional practices that are not restricted to Design, asthey are necessary for any activities that intend that everyone who is in them involved participating. During the interview, it was verified how the adoption of the participatory designconcepts presents itself as a challenging practice, both in the educational field and in theperspective of its performance in other fields of knowledge. Finally, it should be noted that,about the technical aspects of the interview, it was conducted through the Jitsi Meet videoconference platform, and lasted approximately 40 minutes, recorded via an audio application,available for Android system - and, subsequently, it was transcribed and organized accordingto the norms of the language, having its approval for publication by the interviewed teacher.